2008
DOI: 10.3174/ajnr.a1353
|View full text |Cite
|
Sign up to set email alerts
|

MR Angiography Follow-Up 5 Years after Coiling: Frequency of New Aneurysms and Enlargement of Untreated Aneurysms

Abstract: BACKGROUND AND PURPOSE:Patients with intracranial aneurysms are at risk for future development of new aneurysms and growth of additional untreated aneurysms. Because in previous long-term studies duration of follow-up varied widely, the time interval after which screening could be effective remains largely unknown. The purpose of this study was to assess the incidence of de novo aneurysm formation and the growth of additional untreated aneurysms in patients with coiled aneurysms followed up with MR angiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…In a study of adult patients imaged with 3T MRA 5 years after brain aneurysm coiling, 1.54% had de novo aneurysms. 7 In a study of adult patients having undergone ICA occlusion for aneurysm treatment, 3T MRA at a mean of 50.3 months after takedown (range, 0 -107 months), showed no de novo aneurysms. 8 Our current study relies on catheter angiographic imaging follow-up, which may be more sensitive than 3T MRA for small aneurysms.…”
Section: Discussionmentioning
confidence: 95%
“…In a study of adult patients imaged with 3T MRA 5 years after brain aneurysm coiling, 1.54% had de novo aneurysms. 7 In a study of adult patients having undergone ICA occlusion for aneurysm treatment, 3T MRA at a mean of 50.3 months after takedown (range, 0 -107 months), showed no de novo aneurysms. 8 Our current study relies on catheter angiographic imaging follow-up, which may be more sensitive than 3T MRA for small aneurysms.…”
Section: Discussionmentioning
confidence: 95%
“…The same observation was made in a recent surgical study. 23 Sprengers et al 11,20 found an incidence of de novo aneurysms in 1.5% of patients after 5 years. De novo aneurysms are extremely rare, but we should continue to follow all patients to proactively detect these malformations.…”
Section: Retreatmentmentioning
confidence: 99%
“…Decision to treat was made by consensus by the referring neurosurgeon and the interventional physician. The severity of subarachnoid hemorrhage was clinically assessed at the time of admission by using the Hunt and Hess (HH) grading scale 11 and the Fisher scale. For the HH scale, 18% of patients were admitted with clinical grade I (n ϭ 159); 40%, with grade II (n ϭ 312); 16%, with grade III (n ϭ 136); and 26%, with grade IV (n ϭ 197).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-one studies reported risk factors for aneurysm growth, including 3954 patients with 4990 aneurysms with 11,000 patient-years and 13,294 aneurysm-years of follow-up. 9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Eleven of these studies reported the rupture rate of growing aneurysms. Mean patient follow-up was 4.9 years, and median was 3.2 years.…”
Section: Literature Reviewmentioning
confidence: 99%